Repeatability of SUV measurements in serial PET - Schwartz, J. (Med Phys, 2011)
PURPOSE: : The standardized uptake value (SUV) is a quantitative measure of FDG tumor uptake frequently used as a tool to monitor therapeutic response. This study aims to (i) assess the reproducibility and uncertainty of SUV(max) and SUV(mean), due to purely statistical, i.e., nonbiological, effects and (ii) to establish the minimum uncertainty below which changes in SUV cannot be expected to be an indicator of physiological changes. METHODS: : Three sets of measurements were made using a GE Discovery STE PET/CT Scanner in 3D mode: (1) A uniform(68)Ge 20 cm diameter cylindrical phantom was imaged. Thirty serial frames were acquired for durations of 3, 6, 10, 15, and 30 min. (2) Esser flangeless phantom (Data Spectrum, ∼6.1 L) with fillable thin-walled cylinders inserts (diameters: 8, 12, 16, and 25 mm; height: ∼3.8 mm) was scanned for five consecutive 3 min runs. The cylinders were filled with (18)FDG with a 37 kBq/cc concentration, and with a target-to-background ratio (T/BKG) of 3/1. (3) Eight cancer patients with healthy livers were scanned ∼1.5 h post injection. Three sequential 3 min scans were performed for one bed position covering the liver, with the patient and bed remaining at the same position for the entire length of the scan. Volumes of interest were drawn on all images using the corresponding CT and then transferred to the PET images. For each study (1–3), the average percent change in SUV(mean) and SUV(max) were determined for each run pair. Moreover, the repeatability coefficient was calculated for both the SUV(mean) and SUV(max) for each pair of runs. Finally, the overall ROI repeatability coefficient was determined for each pair of runs. RESULTS: : For the(68)Ge phantom the average percent change in SUV(max) and SUV(mean) decrease as a function of increasing acquisition time from 4.7 ± 3.1 to 1.1 ± 0.6%, and from 0.14 ± 0.09 to 0.04 ± 0.03%, respectively. Similarly, the coefficients of repeatability also decrease between the 3 and 30 min acquisition scans, in the range of 10.9 ± 3.9% – 2.6 ± 0.9%, and 0.3 ± 0.1% – 0.10 ± 0.04%, for the SUV(max) and SUV(mean), respectively. The overall ROI repeatability decreased from 18.9 ± 0.2 to 6.0 ± 0.1% between the 3 and 30 min acquisition scans. For the (18)FDG phantom, the average percent change in SUV(max) and SUV(mean) decreases with target diameter from 3.6 ± 2.0 to 1.5 ± 0.8% and 1.5 ± 1.3 to 0.26 ± 0.15%, respectively, for targets from 8 – 25 mm in diameter and for a region in the background (BKG). The coefficients of repeatability for SUV(max) and SUV(mean) also decrease as a function of target diameter from 7.1 ± 2.5 to 2.4 ± 0.9 and 4.2 ± 1.5 to 0.6 ± 0.2, respectively, for targets from 8 mm to BKG in diameter. Finally, overall ROI repeatability decreased from 12.0 ± 4.1 to 13.4 ± 0.5 targets from 8 mm to BKG in diameter. Finally, for the measurements in healthy livers the average percent change in SUV(max) and SUV(mean) were in the range of 0.5 ± 0.2% – 6.2 ± 3.9% and 0.4 ± 0.1 and 1.6 ± 1%, respectively. The coefficients of repeatability for SUV(max) and SUV(mean) are in the range of 0.6 ± 0.7% – 9.5 ± 12% and 0.6 ± 0.7% – 2.9 ± 3.6%, respectively. The overall target repeatability varied between 27.9 ± 0.5% and 41.1 ± 1.0%. CONCLUSIONS: : The statistical fluctuations of the SUV(mean) are half as large as those of the SUV(max) in the absence of biological or physiological effects. In addition, for clinically applicable scan durations (i.e., ∼3 min) and FDG concentrations, the SUV(max) and SUV(mean) have similar amounts of statistical fluctuation for small regions. However, the statistical fluctuations of the SUV(mean) rapidly decrease with respect tothe SUV(max) as the statistical power of the data grows either due to longer scanning times or as the target regions encompass a larger volume.